2015
DOI: 10.1007/s00526-015-0904-4
|View full text |Cite
|
Sign up to set email alerts
|

Fractional porous media equations: existence and uniqueness of weak solutions with measure data

Abstract: We prove existence and uniqueness of solutions to a class of porous media equations driven by the fractional Laplacian when the initial data are positive finite Radon measures on the Euclidean space R d . For given solutions without a prescribed initial condition, the problem of existence and uniqueness of the initial trace is also addressed. By the same methods we can also treat weighted fractional porous media equations, with a weight that can be singular at the origin, and must have a sufficiently slow deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…The previous authors also showed that in the presence of highly decaying weights, like ρ(x) ≤ C|x| −γ with γ > n, the long-term behavior of the solutions completely departs from the non-weighted case; indeed, solutions tend to stabilize to a constant value all over the space. This and other surprising results have led to a keen interest in the subject with contributions by many authors, like [18,22,20,29,40,26,27,37]. The properties and long-time behavior of the solutions in the presence of weights that decay in a slower way than |x| −n have been investigated in particular by Reyes and the author in a series of papers [41][42][43].…”
Section: Asymptotics For Weighted Nonlinear Diffusionmentioning
confidence: 97%
“…The previous authors also showed that in the presence of highly decaying weights, like ρ(x) ≤ C|x| −γ with γ > n, the long-term behavior of the solutions completely departs from the non-weighted case; indeed, solutions tend to stabilize to a constant value all over the space. This and other surprising results have led to a keen interest in the subject with contributions by many authors, like [18,22,20,29,40,26,27,37]. The properties and long-time behavior of the solutions in the presence of weights that decay in a slower way than |x| −n have been investigated in particular by Reyes and the author in a series of papers [41][42][43].…”
Section: Asymptotics For Weighted Nonlinear Diffusionmentioning
confidence: 97%
“…We recall now some well posedness results proved in [23]. In fact, thanks to the theory developed therein, we can guarantee existence and uniqueness of weak solutions to (3) (according to Definition 2.4).…”
Section: 2mentioning
confidence: 95%
“…(i) The smoothing effect (20) can be proved as in [23,Proposition 4.6]. In fact, such proof only relies on the validity of the fractional Sobolev inequality…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…As regards weighted porous medium equations, in [34] L q0 -L p smoothing effects (with p ∈ (q 0 , ∞)) were established by only assuming a (spectral-gap) Poincaré inequality, which in general prevents L ∞ regularization. As for the fractional porous medium equation on Euclidean space, we quote [22] and [36], where fractional Gagliardo-Nirenberg-type (or Nash-type) inequalities were used. In [14], the same equation was considered on domains with homogeneous Dirichlet boundary conditions, and smoothing effects were proved by means of smart Green-function techniques.…”
Section: Introductionmentioning
confidence: 99%